2015
DOI: 10.3823/1743
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial low-level laser therapy may improve alertness and awareness in traumatic brain injured subjects with severe disorders of consciousness: a case series

Abstract: Background:Transcranial low-level laser therapy (T-LLT) proved promising in acute stroke studies and in single traumatic brain injured subjects (TBI). It was assumed to increase cortical mitochondrial energy production and/or vasodilatation.Objective: Within this case series the potential of transcranial lowlevel laser therapy in improving the alertness and awareness in TBI subjects with severe disorders of consciousness will be investigated. Methods:Following a 21-day baseline, the forehead of five patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…When PBM is applied to the head, it is called photoneuromodulation (PNM) and can be used to improve brain function 1 . Studies on PNM have shown positive effects on patients with dementia 2 4 , traumatic brain injury 5 8 , stroke 9 12 , and depression 13 15 . Specifically, PNM in patients with traumatic brain injury 5 , 6 showed improvement in executive functioning, verbal learning, and memory after several sessions of treatment provided over several weeks to years.…”
Section: Introductionmentioning
confidence: 99%
“…When PBM is applied to the head, it is called photoneuromodulation (PNM) and can be used to improve brain function 1 . Studies on PNM have shown positive effects on patients with dementia 2 4 , traumatic brain injury 5 8 , stroke 9 12 , and depression 13 15 . Specifically, PNM in patients with traumatic brain injury 5 , 6 showed improvement in executive functioning, verbal learning, and memory after several sessions of treatment provided over several weeks to years.…”
Section: Introductionmentioning
confidence: 99%
“…they stimulated the cortex of five subjects, four of them are chronic with unresponsive attentiveness or minimal awareness, and one patient subacute with a kinetic mutism, with the transcranial laser (785 nm, 10 mW/cm2, continuous wave mode, 21 emitting diodes) for ten minutes every workday for 6 weeks. Their results supported that TLT had been found to improve the patients' alertness and awareness [38]. The second explanation for the nonsignificant difference between groups regarding P22-N30 may be attributed to that application of laser did not exert an analgesic effect as patients with neck pain had a significantly higher joint position sense error than healthy controls (De Vries and others in 2015) which in turn affects somatosensory integration [39].…”
Section: Discussionmentioning
confidence: 75%
“…In 2015, Hesse et al reported the use of low-level lasers with a wavelength of 785 nm, continuous wave, and 10 mW/cm 2 power density over 10 weeks on four chronic patients in a state of unresponsive wakefulness or minimal consciousness and one subacute patient in the state of akinetic mutism (total of five patients). In summary, the treatment protocol improved the patients’ alertness and awareness, but epileptic fits were potential side effects [ 77 ].…”
Section: Clinical Data On Pbm Effects On Human Tbimentioning
confidence: 99%